(untitled) (Tanzania Journal for Population studies and Development, 2018)
This study examined the stakeholders’ perception of the University of Dar es Salaam’s senior management capability in managing students’ crises. We purposively selected two governmental agencies—the Higher Education Students’ Loan Board (HESLB) and the Tanzania Commission for Universities (TCU)—and the Ministry of Education and Vocational Training (MoEVT), two political parties, eight students and eight students’ organisation leaders. This study was informed by Littlejohn’s (2002) Compliance Gaining Theory, which suggests that using strategies such as reward, punishment, both positive and negative can enable the university administration to gain the compliance of the students. This study found that the university’s management neither actively involved academic staff nor students in the management of students’ disturbances. As a result, the university ended up being perceived rather negatively even for problems occasioned by external forces over which it technically has no absolute control. Thus, the University should have an effective internal and external communication strategy to ensure that it remains in good books, and is perceived positively even during students’ crises, which in themselves should not be treated negatively.